Clinical Characteristics and Mortality Risk Factors in Patients with Tuberculosis and Coincident Pneumocystis jirovecii Pneumonia: A Retrospective Single-Center Study - Pan X; Zheng J; Xu J; Pan L; Wang C; Huang X; Qiu J; Yan C; Mao M (Infection and Drug Resistance)
Xiaohong Pan,1 Jun Zheng,2 Jiekun Xu,1 Lei Pan,1 Caihong Wang,1 Xiaoqing Huang,1 Junke Qiu,1 Chenxi Yan,1 Minjie Mao1 1Department of Intensive Care Unit for Tuberculosis, Zhejiang Tuberculosis Diagnosis and Treatment Center, Zhejiang Hospital of Integrated Traditional Chinese and Western Medicine, Hangzhou, Zhejiang, 310013, People’s Republic of China; 2Department of Rehabilitation, Health Service Center of Nanxing Subdistrict, Hangzhou, Zhejiang, 310000, People’s Republic of ChinaCorrespondence: Minjie Mao, Department of Intensive Care Unit for Tuberculosis, Zhejiang Tuberculosis Diagnosis and Treatment Center, Zhejiang Hospital of Integrated Traditional Chinese and Western Medicine, No. 208 huancheng Road, Hangzhou, Zhejiang, 310013, People’s Republic of China, Tel +8615825500408, Email pansaide@foxmail.comIntroduction: HIV infection and immunosuppressive therapy are major risk factors for tuberculosis (TB) or Pneumocystis jirovecii pneumonia (PJP). The joint presence of these diseases is not rare, posing substantial challenges in diagnosis and treatment. This study examined the clinical characteristics of patients with coincident TB and PJP and identified the associated mortality risk factors.Methods: Patients diagnosed with TB and PJP at our center between January 2018 and December 2023 were retrospectively investigated. Data on demographics, diagnostic methods, clinical symptoms, imaging findings, laboratory examinations, treatment regimens, and clinical outcomes were collected from electronic medical records and summarized. The risk factors for mortality were then explored by logistic regression analysis, and the corresponding odds ratios (ORs) and 95% confidence intervals (CIs) were calculated.Results: In total, 26 patients were included (mean age, 61.6 ± 16.6 years; illness duration, 39.8 ± 53.1 days). All cases of PJP were diagnosed by next-generation sequencing. The most common symptoms were cough (88.5%), fever (84.6%), and shortness of breath (69.2%). Chest imaging predominantly revealed ground-glass opacities (57.7%). Six patients (23.1%) died during hospitalization. Multivariate analysis identified the oxygenation index (OR = 0.979, 95% CI = 0.976– 0.982) and lymphocyte count (OR = 0.006, 95% CI = 0.002– 0.017) as independent risk factors for mortality.Conclusion: Favorable clinical outcomes can be expected in most cases of coincident TB and PJP. However, decreases in the oxygenation index and lymphocyte count increase the risk of mortality.Keywords: tuberculosis, Pneumocystis jirovecii pneumonia, prognosis, risk factors